Resíduos sólidos nas escolas públicas estaduais no município de Bragança, Pará - FIGUEIRÓ, Nathálya Rafaelle Brito (2024)
Throughout history, the production of solid waste has become an intrinsic part of human life, and its progressive increase over the centuries has impacted the relationship between living beings and the environment. In schools, where a variety of waste is generated, the need for an adequate management plan becomes essential. This study aims to characterize solid waste management is state schools in Bragança, Pará, with the intention of contributing to the development of na integrated municipal plan. The specific objectives include identifying the types of waste generated, evaluating the current management system and understanding the perception of managers and teachers on the issue of solid waste in schools. Five state schools were selected based on criteria such as distance between them and the diversity of activities carried out, using a qualitative- quantitative descriptive approach and data was collected through semi-structured questionnaires applied to managers and teachers, complemented by on-site observations. Five managers (three directors and two vice directors) and Twenty teachers from different areas of knowledge participated, all of whom had previously consented through an Informed Consent Form. All managers mentioned paper as the waste most generated in schools, followed by plastic and organic waste. When teachers were asked, paper was also the most common, followed by organic and plastic waste. The results showed that paper, plastic and organic waste. When teachers were asked, paper was also the most common, followed by organic waste and plastic. The results showed that paper, plastic and organic waste are the most common waste in schools, with suggestions that recycling practices can be effective in all schools. When asked whether the school has a Solid Waste Management plan, 60% of teachers are unaware of the existence of a PGRS, the remainder report that even though they have management, the waste has the same Destination. These conclusions highlight the need for eficiente solid waste management in schools and the promotion of environmental awareness and education to move towards a more sustainable Society.